Penyuluhan Kewirausahaan Pada Pelaku Usaha Mikro dan Kecil Jagung Rebus Di Desa Amesiu Kecamatan Pondidaha - Anto, Rola Pola; Gunawan, Gunawan; Amir, Muhammad; Habiba, Nurul; Saputri, Atisah; Sabar, Andi; Zaeroni, Muh (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This counseling was carried out in Amesiu Village, Pondidaha District, Konawe Regency. The purpose of this counseling is to provide entrepreneurial information to culinary business actors of corn on the cob in Amesiu Village. The method used is observation, lecture method, and documentation method. This entrepreneurship counseling was carried out through the observation stage of the location of the Boiled Corn Culinary Business in Amesiu Village to find out the condition of the boiled corn culinary business stalls. The following steps are to make preparations, namely in the form of location extension permit documents, facilities and infrastructure to be used at the Amesiu Village hall. The implementation stage is the presentation of material by resource persons. The final stage of counseling is to evaluate through question and answer to find out the participants' responses. The results achieved in entrepreneurship counseling for culinary business actors of corn on the cob in Amesiu Village were that the participants succeeded in obtaining important information about good business methods and strategies. In addition, participants can add insight, knowledge and skills in doing business so that they can be successful. As a follow-up to extension activities, it is necessary to carry out entrepreneurial training activities related to service strategies, marketing, packaging of boiled corn products so that they are attractive to visitors. Keywords: Extension; Entrepreneurship; Businessmen; Boiled corn